1989
DOI: 10.1111/j.1365-2125.1989.tb03542.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective disposition of flecainide in relation to the sparteine/debrisoquine metaboliser phenotype.

Abstract: 1 The disposition of the enantiomers of the antiarrhythmic drug flecainide has been studied in five extensive (EM) and five poor (PM) metabolisers of sparteine/debrisoquine after administration of 50 mg of racemic flecainide acetate under conditions of high urinary flow rate and acidic urinary pH. 2 In the EM subjects there were no significant differences in the oral clearance, half-life or urinary excretion of (+)-S-and (-)-R-flecainide. 3 In the PM subjects differences in the pharmacokinetics of S-and R-flec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…This suggests that the main enzyme that metabolizes flecainide is CYP2D6. Some reports, however, have suggested that other CYP isozymes are involved in flecainide metabolism, because MODF and MODLF can be detected in plasma even in CYP2D6 PMs [7–9], although the responsible enzymes have not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the main enzyme that metabolizes flecainide is CYP2D6. Some reports, however, have suggested that other CYP isozymes are involved in flecainide metabolism, because MODF and MODLF can be detected in plasma even in CYP2D6 PMs [7–9], although the responsible enzymes have not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…. The calculated pharmacokinetic parameters listed in Table were in accordance with previous reports (Gross et al ., , ). S / R ratios of elimination half‐life, AUC 0–24 , and amount excreted in urine were lowest in subject 3.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of the assay was sufficient to determine flecainide enantiomers in pharmacokinetic study and routine therapeutic drug monitoring (TDM; Tables and ) compared with previous indirect (Turgeon et al ., ) and direct (Hanada et al ., ) methods equipped with fluorescence detector. Assay precision was confirmed in intra‐ and inter‐day validation experiments and was also comparable with that of previous methods (Table ; Gross et al ., ; Alessi‐Severini et al ., ; Turgeon et al ., ; Hanada et al ., ). Therefore, the present method is sufficiently sensitive and precise in the concentration range required for pharmacokinetic study and flecainide TDM (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…It follows that the influence of the sparteine/debrisoquine polymorphism on flecainide disposition may be particularly important in patients with renal impairment. Although small differences in the stereoselective disposition of flecainide have been observed between phenotypes (Gross et al 1989), they should not contribute to differences in response between poor and extensive metabolisers, since the enantiomers have similar antiarrhythmic potency. Data are lacking on the relationship between polymorphic oxidation and the clinical response to flecainide.…”
Section: Cardiovascular Drugsmentioning
confidence: 95%